Al-Amwal According to the Qur’an: Using the Maudhu’i Method - Sahabi, Ansar; Baide, Kartini (Talaa : Journal of Islamic Finance, 2021)
This study aims at describing the concept of al-amwal in the Qur'an which is referred to as treasure. This research focuses more on the concept of property and property ownership in the Qur'an, property as slander (trials), worldly treasures (al-hayah al-dunya), property as a means of doing good. Descriptive research method with qualitative approach is employed in this study. This present study, is a library study using maudhu’i method. Maudhu’i method is a method seeks to find the answer in the Qur'an by collecting ayahs of the Qur'an that have similar purpose, which together discuss a particular topic / title and publish those ayah in accordance with the time of thier descent in accordance with the causes of their descent, then pay attention to the ayahs with explanation, description and relationship with other ayahs. The results show that wealth (wealth) is a primary need for man to support his life in this world. The Qur'an reminds that property must be obtained through lawful manners as stipulated by the shariah law. In fact the Qur'an and the Sunnah clearly explain that property should not be transferred from one person to another through unjustified ways. In stead, it should be transferred based on the sharia, such as through trades or other lawful transactions. The use of property in Islamic teachings must always be in devotion to God and used in the framework of taqqarub (to get closer) to Allah.